Oral Administration of TAT-PTD–Diapause Hormone Fusion Protein Interferes With Helicoverpa armigera (Lepidoptera: Noctuidae) Development. Issue 1 (28th August 2015) - Zhou, Zhou; Li, Yongli; Yuan, Chunyan; Zhang, Yongan; Qu, Liangjian
Abstract : Diapause hormone (DH), which can terminate diapause in Helicoverpa armigera Hübner (Lepidoptera: Noctuidae), has shown promise as a pest control method. However, the main challenge in using DH as an insecticide lies in achieving effective oral delivery, since the peptide may be degraded by digestive enzymes in the gut. To improve the efficacy of oral DH application, the Clostera anastomosis (L.) (Lepidoptera: Notodontidae) diapause hormone (caDH) was fused to the Protein Transduction Domain (PTD) of the human immunodeficiency virus-1 transactivator of transcription (TAT). Cellular transduction of TAT-caDH was verified with the use of a green fluorescent protein fusion, and its ability to terminate diapause was verified by injection into diapausing H. armigera pupae. Orally administered TAT-caDH resulted in larval growth inhibition. In TAT-caDH–treated insects, larval duration was delayed and the pupation rates were decreased at both development promoting conditions [27°C, a photoperiod of 14:10(L:D) h] and diapause inducing conditions [20°C, a photoperiod of 10:14(L:D) h]. No significant difference in diapause rate was observed between the TAT-caDH–treated and caDH-treated or control pupae maintained at diapause inducing conditions. Our results show that treatment with a recombinant TAT-caDH protein can affect larval development in H. armigera, and it suggest that TAT-DH treatment may be useful for controlling pests. This study is the first record of oral DH application in insect.